2017
DOI: 10.1186/s13028-017-0291-2
|View full text |Cite
|
Sign up to set email alerts
|

Cervid herpesvirus 2 and not Moraxella bovoculi caused keratoconjunctivitis in experimentally inoculated semi-domesticated Eurasian tundra reindeer

Abstract: BackgroundInfectious keratoconjunctivitis (IKC) is a transmissible disease in semi-domesticated Eurasian reindeer (Rangifer tarandus tarandus). It is regarded as multifactorial and a single causative pathogen has not yet been identified. From clinical outbreaks we have previously identified Cervid herpesvirus 2 (CvHV2) and Moraxella bovoculi as candidates for experimental investigations. Eighteen reindeer were inoculated in the right eye with CvHV2 (n = 5), M. bovoculi (n = 5), CvHV2 and M. bovoculi (n = 5) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 30 publications
10
30
0
Order By: Relevance
“…In a natural outbreak of IKC in reindeer, the virus was most often detected and isolated at higher titers, from animals with mild or early stage signs of IKC and only from a few animals with severe signs. It was hypothesized that the peak of viral replication and shedding occurred at earlier stages, whereas secondary bacterial infections were dominant in later stages of the disease [ 15 , 21 ]. It is also possible that the virus, during the late stages of IKC, is entering the latency stage, shutting down the active replication cycle and the shedding of progeny virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a natural outbreak of IKC in reindeer, the virus was most often detected and isolated at higher titers, from animals with mild or early stage signs of IKC and only from a few animals with severe signs. It was hypothesized that the peak of viral replication and shedding occurred at earlier stages, whereas secondary bacterial infections were dominant in later stages of the disease [ 15 , 21 ]. It is also possible that the virus, during the late stages of IKC, is entering the latency stage, shutting down the active replication cycle and the shedding of progeny virus.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 – 20 ], which all may play a role in the development of the disease. However, from an outbreak of IKC in reindeer it was concluded that Cervid herpesvirus 2 (CvHV2) was the causative and transmissible agent, accompanied by secondary opportunistic bacterial infections [ 15 ] and it has recently been shown experimentally that CvHV2, alone and in combination with Moraxella bovoculi, was able to cause clinical sympotms characteristic for IKC in reindeer [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent controlled challenge experiment, we found that CvHV2 causes IKC in previously unexposed and seronegative semi-domesticated reindeer [20]. Animals inoculated with CvHV2, alone or in combination with the gram-negative bacterium M. bovoculi, developed clinical signs of IKC within two days after inoculation of the virus, and displayed conjunctival edema, hyperemia, and purulent exudate.…”
Section: Introductionmentioning
confidence: 94%
“…Moraxella bovoculi did not produce clinical signs in this controlled challenge experiment, except for a transient grey or whitish ocular discharge on the day of inoculation. In the present paper, we present the detailed histopathology of eye tissues collected from the previous challenge experiment [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation